Crystallization of nepenthesin I using a low-pH crystallization screen - Fejfarová, Karla; Kádek, Alan; Mrázek, Hynek; Hausner, Jiří; Tretyachenko, Vyacheslav; Koval', Tomáš; Man, Petr; Hašek, Jindřich; Dohnálek, Jan (Acta crystallographica. Section F, Structural biology communications, 2016)
Nepenthesins are aspartic proteases secreted by carnivorous pitcher plants of the genus Nepenthes. They significantly differ in sequence from other plant aspartic proteases. This difference, which provides more cysteine residues in the structure of nepenthesins, may contribute to their unique stability profile. Recombinantly produced nepenthesin 1 (rNep1) from N. gracilis in complex with pepstatin A was crystallized under two different crystallization conditions using a newly formulated low-pH crystallization screen. The diffraction data were processed to 2.9 and 2.8 Å resolution, respectively. The crystals belonged to space group P212121, with unit-cell parameters a = 86.63, b = 95.90, c = 105.40 Å, α = β = γ = 90° and a = 86.28, b = 97.22, c = 103.78 Å, α = β = γ = 90°, respectively. Matthews coefficient and solvent-content calculations suggest the presence of two molecules of rNep1 in the asymmetric unit. Here, the details of the crystallization experiment and analysis of the X-ray data are reported.
Keywords: Plant Proteins; Pepstatins; Magnoliopsida; Crystallography, X-Ray; Nepenthes gracilis; koncentrace vodíkových iontů; low-pH crystallization screen; aspartic proteases; Aspartic Acid Endopeptidases; krystalografie rentgenová; Hydrogen-Ion Concentration; Crystallization; pepstatiny; nepenthesins; krystalizace; aspartátové endopeptidasy; rostlinné proteiny